Maximum Potential Score (MPS): An operating model for a successful customer-focused strategy - Cabello-González, José Manuel; Galguera, Laura; Ruíz-De la Rúa, Francisco (Revista Electrónica de Comunicaciones y Trabajos de ASEPUMA, 2015)
One of marketers’ chief objectives is to achieve customer loyalty, which is a key factor for profitable growth. Therefore, they need to develop a strategy that attracts and maintains customers, giving them adequate motives, both tangible (prices and promotions) and intangible (personalized service and treatment), to satisfy a customer and make him loyal to the company. Finding a way to accurately measure satisfaction and customer loyalty is very important. With regard to typical Relationship Marketing measures, we can consider listening to customers, which can help to achieve a competitive sustainable advantage. Customer satisfaction surveys are essential tools for listening to customers. Short questionnaires have gained considerable acceptance among marketers as a means to achieve a customer satisfaction measure. Our research provides an indication of the benefits of a short questionnaire (one/three questions). We find that the number of questions survey is significantly related to the participation in the survey (Net Promoter Score) or NPS. We also prove that a the three question survey is more likely to have more participants than a traditional survey (Maximum Potential Score or MPS) . Our main goal is to analyse one method as a potential predictor of customer loyalty. Using surveys, we attempt to empirically establish the causal factors in determining the satisfaction of customers. This paper describes a maximum potential operating model that captures with a three questions survey, important elements for a successful customer-focused strategy. MPS may give us lower participation rates than NPS but important information that helps to convert unhappy customers or just satisfied customers, into loyal customers.